STRATEGI PUBLIC RELATIONS DALAM MENINGKACITRA PERGURUAN TINGGI SWASTA DI JA Studi Kasus Perguruan Tinggi Swasta di Universitas Pembangunan Nasional Veteran Jawa Timur) - Teguh Hidayatul Rachmad (Jurusan Ilmu Komunikasi UTM, 2015)
The strategy is a means or tool to achieve long-term goals in accordance withthe vision and mission agencies. Public relations is the process or activity that aims to establish communication between the organization and external parties and within the organization. The image is the overall impressionformed the minds of the public agency. So when put together, then the sense ofPublic Relations Strategy, which is how the effort to achieve the specified goalor purpose in accordance with the wishes continuously deliberately, in orderto establish and maintain mutual understanding between the organization andits publics.Issues examined in this study are: “Public Relations Strategies in Improving theimage of Private Higher Education in East Java (Case Study of Private HigherEducation in National Development University” Veteran “East Java)? “. Theresearch method used was qualitative research methods. Merely descriptiveresearch describing situations and events. Data collection techniques usedis through depth interview, observation and documentation. This type ofsampling used was purposive sample of the sample aimed to choose certainpeople who are considered able to represent the population, are expected tobe able to answer the research problem.From the results of this study was obtained that the Strategic Public Relations, UPN “Veteran” East Java in Improving the image using the two conceptsof strategic marketing and public relations strategies. Both strategies areanalyzed from internal and external. This study concluded that the PublicRelations Strategy UPN “Veteran” East Java in Improving image is effective,but must be supplemented by a strategy closer to the target market college, inthis case is prospective students. Image enhancement can also be achieved byimproving the quality of service and facilities as well as spiritual guidance toall the academic community, particularly students Key words : Strategy, Public Relations, Image